Hot water epilepsy (HWE) familial and nonfamilial case reports - (:unkn) unknown (My University, 2005)
Reflex epilepsy is a form of epilepsy precipitated by a specific stimulus and events. Seizure precipitation by hot water during bathing is named as "hot water" or "bathing epilepsy" which is a rare and unique form of reflex epilepsy. It is especially common in Southern India and of higher frequency in Muslims among them. There are also isolated and rare case reports from Australia, Japan, Canada and the United States. A small series of patients with hot water epilepsy (HWE) was reported from Turkey. The cases with HWE may be sporadic or familial. Our aim is to outline the clinical and electroencephalographic (EEG) features of four patients with hot water epilepsy, seen at our clinic. One of our patients has a family history of epilepsy. The second and third generation of family members had seizures during bathing. It is important to ask patients with HWE about bathing habits (pouring hot water over the head from a bowl), the temperature and amount of bathing water, the duration of bathing, any additional spontaneous seizures and family history. Sometimes this is enough to eliminate precipitating factors for treatment.
Keywords: Hot water; Pathophysiology; Reflex epilepsy; Treatment